Enhancemen Effect of Hydrogen Sulfide Over Metal Ion-Exchange Mesoporous Silicate FSM-16 for Acid Catalyzed Reactions. - Lebong Andalaluna; Masatoshi Sugioka (ASEAN Journal of Chemical Engineering, 2005)
The activity enhancement of metal ion-exchange mesoporous silicate FSM-16 (MeFSM-16) by sulfiding with hydrogen sulfide was studied using acid-catalyzed reactions, isomerization of I-butene, cis-2-butene and cyclopropane, as model reactions. It was revealed that the catalytic activities of MeFSM-16 for the acid-catalyzed reactions were remarkably enhanced after sulfiding with hydrogen sulfide. Moreover, it was observed that the optimum enhancement effect of hydrogen sulfide was obtained at the sulfiding temperature of 200°C. Infrared spectroscopic measurement of pyridine adsorption over sulfided MeFSM-16 showed that the activity enhancement of MeFSM-16 resulted in the generation of new Bronsted acid sites. Keywords: Metal ion-exchange, mesoporous silicate, hydrogen sulfide, and activity enhancement.